DAYA SAING PRODUKSI BAWANG MERAH VARIETAS LOKAL RUBARU PASCA KEBIJAKAN SUBSIDI PUPUK 2022 - Laily Yusnita Noviandika; Elys Fauziyah; Aminah Happy Moninthofa Ariyani (Universitas Sebelas Maret, 2024)
The government has issued a new policy regarding subsidized fertilizer regulated in Minister of Agriculture Regulation Number 10 of 2022. This causes the production costs borne by Rubaru Shallot farmers to be higher because the government subsidizes only two types of fertilizer. This condition can cause the competitiveness of shallots to decrease. This research aims to analyze the impact of changes in the fertilizer subsidy policy in 2022 on the Rubaru Local Variety Red Onion farming and its competitive and comparative advantages. The research location was determined purposively in Mandala Village. The total research sample was 42 people taken using the purposive sampling method. The data type used is primary data, which includes input prices, output prices, and profits in the form of market and social prices. Data analysis uses the Policy Analysis Matrix (PAM) model. The results of the analysis and discussion show that in general, the impact of the 2022 fertilizer subsidy change policy will still benefit farmers because even though the intervention reduces the profits obtained. Other results show that after these policy changes, the Rubaru Variety Shallot Farming in Mandala Village still has competitive and comparative competitiveness.